DOWN SYNDROME AND ITS AGE-RELATED CHARACTERISTICS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article provides information on the origins, history, causes, clinical presentation, etiology, age-related characteristics, and developmental stages of Down syndrome.